Pesticide residues in water from TPC sugarcane plantations and environs, Kilimanjaro region, Tanzania - Hellar, H; Kishimba, MA (Tanzania Journal of Science, 2021)
We report herein, the analysis of water samples collected from TPC Sugarcane Plantation and its environs in Kilimanjaro region, which is the earliest intensive user of pesticides in Tanzania. A total of 50 water samples collected from 18 sampling sites between 2000 and 2001 were analyzed for pesticide residues. The organochlorines aldrin, dieldrin, heptachlor epoxide, HCHs, endosulfans and DDTs were detected with mean concentrations ranging from 1.1 to 636.7 ng/l. DDT and its metabolites were the most dominant in the detected residues whereas the endosulfans were the least dominant The residues' concentrations were higher in the sugarcane fields than in the environs, although the fresh use of banned pesticides was evident in samples collected from the plantation's environs. In most of the sites, samples had higher concentrations and frequencies during the dry season than the rainy season. It is worth noting that the water from the rivers in the immediate environs of the plantation, which are also used for domestic purposes, had residue levels below the WHO recommended maximum residue levels for drinking water with the exception of River Kikavu.